Implementation of the Policy to Accelerate the Development in Rebana Region, West Java, Indonesia - Supena, Stevy Hanny (LifeSciFi, 2025)
This study investigates the implementation of Presidential Regulation Number 87 of 2021, which aims to accelerate the development in West Java, employing a descriptive qualitative approach, the study gathers data through interviews with government officials, investors, and local communities, as well as field observations. The analysis uses Marilee Grindle’s policy implementation theory, complemented by the Big Push concept and the Public and Government Culture dimensions. Findings show that development progress is still below expectations, with only 9 out of 18 strategic projects completed by 2024. Major challenges include weak inter-agency coordination, limited financial resources, and lack of private sector investment. However, there has been notable improvement in infrastructure and regional connectivity. Economic indicators in West Java reflect positive trends, such as 5.12% economic growth and a poverty rate decline to 6.67% in 2023, although unemployment remains an issue. The study recommends improved coordination, adequate funding, active community participation, and environmental sustainability. By implementing the StevyHanny Model, development can become more inclusive and sustainable, creating greater economic and social benefits for all stakeholders.